Think and act like a doctor - without pipes and tambourines - during the war and COVID-19 - Voloshyna, Larysa (Psychosomatic Medicine and General Practice, 2021)
The world has changed, Ukraine has changed, we have changed, but the world, Ukraine, and we have not become worse. And return to the old, thank God, will not be! A new life and a new order begins in all its fullness and truth. The need for the article is due to the fact that during the war and COVID-19 training and education of young doctors became extremely important. When life and death go hand in hand, when not only theory but also practice becomes more important, when decisions must be made quickly, when there is no oxygen for the patient and no blood for the wounded soldier, all this causes intense thinking in every critical situation. How to find a way out? Do doctors know how to do it? Do they see the same black gorilla? And did she see them, or maybe they even met by sight? The theoretical basis of our study is the achievements of scientists in the field of existential and humanistic psychology at the European and world levels. We have a practical base everywhere: a ward in a hospital, a dugout at the front, and people with their pains and problems everywhere. And the doctor, in addition to knowledge, must still make timely decisions - the only right one, and first save, and only then treat. The experience of doctors and employees, students, patients, statesmen was used in writing the article. The main works on the psychology of thinking, existential psychotherapy, paradoxes and passions in psychotherapy belong to J.-P. Sartre, W. Frankl, E. Dorzen, R. Leing, G.W. Chujko, О.С. Chabanu, O.O. Haustova and others. Presentation of scientific novelty, theoretical and practical significance of the researched problems in training of future doctors, treatment of patients and their rehabilitation during the COVID-19 pandemic and in the post-coding period and rehabilitation of soldiers with post-frontal syndrome was the purpose of the study.